2005
DOI: 10.1159/000087124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fexofenadine Hydrochloride in a Guinea Pig Model of Antigen-Induced Rhinitis

Abstract: Allergic rhinitis is an inflammatory disease of the nasal mucosa, induced by histamine, leukotrienes, and other substances released from mast cells. Fexofenadine hydrochloride, the active metabolite of terfenadine, is a novel, nonsedating antiallergic drug having H1 receptor antagonistic activity. Fexofenadine is effective for the treatment of allergic rhinitis. However, its mechanism of action in attenuating nasal congestion has not yet been elucidated. Therefore, we first examined the effects of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 69 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…In vitro studies have shown that FEX inhibited the production of metalloproteinase (MMP)-2 and MMP-9, as well as MMP mRNA expression and NF-B activation from both nasal polypderived fibroblasts and nasal mucosal fibroblasts in response to tumor necrosis factor-␣ stimulation [27] . FEX also inhibited thymus-and activation-regulated chemokine levels in peripheral blood leukocytes [29] and blocked TX release, thus reducing the increase of nasal airway resistance in a guinea pig model of antigen-induced rhinitis [30] . In our recently published study, it was shown that FEX inhibited the production of arachidonic acid metabolites LTC 4 -LTD 4 -LTE 4 and PGE 2 in cultured human monocytes, but appeared to have no effect on 5-lipoxygenase [17] .…”
Section: Discussionmentioning
confidence: 95%
“…In vitro studies have shown that FEX inhibited the production of metalloproteinase (MMP)-2 and MMP-9, as well as MMP mRNA expression and NF-B activation from both nasal polypderived fibroblasts and nasal mucosal fibroblasts in response to tumor necrosis factor-␣ stimulation [27] . FEX also inhibited thymus-and activation-regulated chemokine levels in peripheral blood leukocytes [29] and blocked TX release, thus reducing the increase of nasal airway resistance in a guinea pig model of antigen-induced rhinitis [30] . In our recently published study, it was shown that FEX inhibited the production of arachidonic acid metabolites LTC 4 -LTD 4 -LTE 4 and PGE 2 in cultured human monocytes, but appeared to have no effect on 5-lipoxygenase [17] .…”
Section: Discussionmentioning
confidence: 95%
“…Terfenadine is an H1 receptor antagonist. It has been reported that terfenadine at the above doses significantly inhibits allergic inflammation of the nasal cavity induced by histamine in guinea pigs (16).…”
Section: Sensitization and Challengementioning
confidence: 93%
“…Then, local sensitization was performed every day. From day 14 to day 27, the egg albumin in physiological saline (1 mg/mL, 10 µL) was dropped into the bilateral nasal cavities with a micropipette (Sakairi et al , 2005; McLeod et al , 2002). On day 20, blood was drawn from all groups via the orbit for the assessment of total immunoglobulin E (IgE).…”
Section: Methodsmentioning
confidence: 99%